Is the euro advantageous : does it foster european feelings - Jonung, Lars.; Conflitti, Cristina; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
The introduction of the euro as a currency in physical existence in January 2002 was a major step in the European integration process. The purpose of this paper is to explore how a representative selection of 12 000 Europeans across all countries in the euro area view the effects of the euro five years after its introduction. The empirical analysis uses multinomial logistic regressions to explore the responses to two questions from the Flash Eurobarometer survey conducted in September 2006. The first question asked if the adoption of the euro was advantageous overall or not. The second one asked if using the euro had made you personally feel a little more European than before or not.
Economic Papers